Progress in Boron Nitride-Based Materials as Catalysts for Energy Storage and Electrochemical Application - Khursheed Ahmad; Tae Hwan Oh (Crystals)
The design and fabrication of energy storage devices and electrochemical sensors are two major research fields. Many research groups are dedicated to the development of high-performance energy storage (super-capacitors) devices and electrochemical sensors for the determination of various substances. Thus, it would be worth summarizing the recent progress in BN and its composites based materials for energy storage and electrochemical sensing applications. Two-dimensional (2D) boron nitride (BN) is a widely used electrode material for optoelectronic and electrochemical applications. Herein, we report the progress on the use of BN and its composite-based electrode materials for the development of energy storage (super-capacitors; SCs) devices and electrochemical sensors. The challenges and future perspectives are also mentioned.